Digital Audio Book for Improving Students’ Listening Skills : (A Case Study at English Class in Tangerang) - Dewi Kania Cahyani; Muin, Abdul; Perdana, Purnama Rika (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2025)
This study aims to improve listening skills of English class in Tangerang through digital audio book. This research method used a quantitative with one group pretest-posttest. The sample of this study is 30 students. This study was conducted by providing three treatments, accompanied by a pretest-posttest. The result shows that the average score of pretest is 43 and the average score of posttest is 73.5 with the gained score between them is 30.5. Based on the calculations, the researcher had obtained a score of degrees of freedom or df = 29, and this study used a degree of significance of 5%. By comparing the observation results of observation score = 0.712 in degrees of significance of 5%, the authors concluded that the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. It means that digital audio books can improve students' listening skills at English class in Tangerang.